Pengembangan LKPD Elektronik Berbasis Problem Based Learning untuk Materi Perubahan Lingkungan Geoheritage Gumuk Pasir - Nida Dwi Handayani; Djukri (Postgraduate, University of Mataram, 2024)
This research aims to determine the development of PBL-based electronic LKPD on environmental change material at Gumuk Pasir Geoheritage and the feasibility of PBL-based electronic LKPD on class X environmental change material at Gumuk Pasir Geoheritage. This research is development research (R&D) using a 4D development model consisting of stages definition, design, development and deployment. This research was only carried out until the development stage. This research was validated internally by media expert lecturers and material experts and externally validated by biology teachers and class X high school students. The results of the research show that based on the assessment of media expert lecturers, a score of 82.13 was obtained in the